The "contrôleuse": recognising the role of the "fixer" in academic and media NGO development partnerships. Issue 2 (17th February 2022) - Heywood, Emma; Harding, Sue-Ann
ABSTRACT: Successful NGO development and academic partnerships have, at their core, effective intercultural and multilingual communication and translation practices and processes, including critical recognition of the role of "fixers", who act as the "interface" between local participants and academic NGO impact-assessment researchers. Examining what we call the "contrôleuse" in development research projects in Burkina Faso, Mali and Niger, we show the need, as in journalism, to critically interrogate this intermediary role. Identifying and incorporating the role into research funding and design can be a simple and practical contribution towards challenging inequalities, including contrôleuse perspectives and increasing participatory impact-assessment and development practices.